Effect of the pile cap length and the soil relative density on the pile cap – pile – dense soil interaction: Experimental investigation - Ali Basha; Sabry Elmorsy; Walid Mansour; Basant Ramadan (Case Studies in Construction Materials, 2024)
In the present study, the RC pile cap-pile-soil interaction was experimentally investigated by testing twelve half-scale RC pile caps. Two main parameters were considered within the experimental program; the first factor was the relative density of the supporting sandy soil. Four models were tested without being rested on soil, while the other eight models were rested on sandy soil with a relative density of 80% or 90%. The second studied factor was the ratio between the spacing between the RC piles and the width of the pile (S/D), which varied within the range of 2.25, 2.5, 2.75, and 3.0. In comparison to the reference models (without underneath soil), the impacts of the examined parameters on the load-midspan deflection responses, cracking, and ultimate loads were investigated. Additionally, the associated settlements, stiffness, ductility, and energy dissipation capacity were also examined. The findings revealed that all RC pile caps exhibited a punching failure mode accompanied by shear cracks, irrespective of whether they were resting on sandy soil or not. On the contrary, the ultimate load of RC pile caps resting on sandy soil, especially with a higher relative density, was incredibly enhanced with respect to models loaded without supporting soil. The gain in the ultimate load of RC pile caps with S/D ratios of 2.25, 2.5, 2.75, and 3.0 was in the range of 5.4–6.7%, 12–16%, 15–21%, and 24–35%, respectively.